Modern maintenance practices: approaches and visions towards condition-based asset health management - Telford, S.; Mazhar, Muhammad llyas; Howard, Ian; McClenaghan, James (Engineers Australia, 2010)
Efficient maintenance management practices are of fundamental importance in ensuring the smooth and safe running of manufacturing systems. Maintaining the plant equipment involves lots of activities and use of resources. The required amount of efforts and resources depends on the type of the equipment being maintained as well as the maintenance management strategy. The commonly used maintenance management approaches are categorized as reactive and pro-active. The proactive condition-based maintenance culture is rapidly replacing the classical reactive repair-focused attitude, thereby resulting in enormous savings in human efforts and resources. This strategy determines the health of a system/plant, such as its deterioration level by continuously monitoring the critical performance or degradation parameters. This approach is getting an increasing attention of researchers and practitioners because of the fact that it is more realistic, economical and highly efficient.This paper explores the existing literature on the development and applications of condition based maintenance (CBM). The recent literature underlines the fact that the role of CBM is critical to the smooth, uninterrupted, efficient and safe running of industrial equipment. Furthermore, a clear understanding of the causes of equipment failure and the likelihood of failure occurring in a given period must be developed if acondition based maintenance program is to be successfully implemented. The intricate and integrated nature of the intelligent maintenance management systems demands specific and carefully prepared CBM programs with real-time condition monitoring data recording, analysis, and decision making to facilitate an accurate understanding of the essential maintenance intervals. This in turn can advance optimised utilization of plant equipment with higher levels of certainty and safety.